Repetitive transcranial magnetic stimulation affects behavior by biasing endogenous cortical oscillations - Hamidi, Massihullah; Slagter, Heleen A.; Tononi, Giulio; Postle, Bradley R. (Frontiers in Integrative Neuroscience, 2009)
A governing assumption about repetitive transcranial magnetic stimulation (rTMS) has been that it interferes with task-related neuronal activity – in effect, by “injecting noise” into the brain – and thereby disrupts behavior. Recent reports of rTMS-produced behavioral enhancement, however, call this assumption into question. We investigated the neurophysiological effects of rTMS delivered during the delay period of a visual working memory task by simultaneously recording brain activity with electroencephalography (EEG). Subjects performed visual working memory for locations or for shapes, and in half the trials a 10-Hz train of rTMS was delivered to the superior parietal lobule or a control brain area. The wide range of individual differences in the effects of rTMS on task accuracy, from improvement to impairment, was predicted by individual differences in the effect of rTMS on power in the alpha-band of the EEG ( 10 Hz): a decrease in alpha-band power corresponded to improved performance, whereas an increase in alpha-band power corresponded to the opposite. The EEG effect was localized to cortical sources encompassing the frontal eye fields and the intraparietal sulcus, and was specific to task (location, but not object memory) and to rTMS target (superior parietal lobule, not control area). Furthermore, for the same task condition, rTMS-induced changes in cross-frequency phase synchrony between alpha- and gamma-band (> 40 Hz) oscillations predicted changes in behavior. These results suggest that alpha-band oscillations play an active role cognitive processes and do not simply reflect absence of processing. Furthermore, this study shows that the complex effects of rTMS on behavior can result from biasing endogenous patterns of network-level oscillations.